Análisis del proceso de enfermedad: variables médicas y psicológicas - Moreno, Pilar; Almonacid, Vicenta; Queipo, Silvia; Lluch, Ana (Psicooncología, 2006)
In this work it is assessed a sample of 44 patients treated in Hematology and Medical Oncology Service of the University Clinical Hospital of Valencia during years 1999-2000. All of them were diagnosed of breast cancer and were going to begin adjuvant chemotherapy treatment. Our objective was to determine those variables that can help to prevent the emotional suffering during disease process. We assessed five periods of disease process, that we considered specially problematic and that need more coping resources, by structured interview. It is studied the importance of a possible association between some medical and psychological variables and coping, the perception of the passing of time in the patients and the perceived familiar/social support. We found significant differences between different assessments phases. It is conclude that the period from the diagnosis to the passage by surgery (radical or conservative) and before beginning chemotherapy is the most difficult phase and where is necessary more specialized attention. In the first follow-up visit the patients have been able to adapt, assimilate the lived situation and they have let back the consequences of the chemotherapy treatments, this improvement is maintained in the second follow-up visit. It does not happen the same when it is present adverse effects of the surgery nor with those patients who have psychological disorders.
Keywords: Breast cancer; Coping; Adjustment; Psychological disorders; Distress; Surgery; Chemotherapy